UPAYA PEMERINTAH KOTA SAWAHLUNTO DALAM MENINGKATKAN WISATAWAN MALAYSIA DAN BELANDA TAHUN 2013-2017 - Wulan Sari Purnama; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain, out government policies in developing the tourism sector of Sawahlunto City and the efforts made to increase Malaysian And dutch Tourist in the city of Sawahlunto. Sawahlunto is a city in the province of west sumatra that has historical tourism dutch heritage. With the existence of historical tourism that is still maintained, it becomes an atrraction for tourist.This research uses the Perspective of Globalization, the level of analysis of nation states, Theory of Public Policy and the concept of international tourism. The method used is a qualitative research method. This analysis is based on data obtained from literature studies and field studies by conducting interviews directly with informants who are considered capable of providing information regarding the problem under study.The results of the research in this paper are that in visiting of Malaysian And dutch Tourist to Sawahlunto City has increased from 2013-2017. The increase in foreign tourist visits is inseparable from the policies of the central government and regional governments that are mutually sustainable. One of the efforts promotion in Netherlands, cooperation between Sawahlunto and Malaka, carried out was by carrying out international events, promoting Sawahlunto as a world cultural heritage, and increasing tourism support facilities.Keyword : Sawahlunto, Malaysian, Dutch, Foreign Tourists, Tourism, Government Policy, Tourism Promotion.